A Monetary Model of Inflation for Bangladesh, 1974-1985 (The Pakistan Development Review, 1989)
A model of inflation for Bangladesh is developed and estimated for the period 1974:2-1985 :4, in line with the monetary approach and based on the hypothesis that any disequilibrium in the real money-market adjusts itself through changes in the price level, but not instantaneously. Changes in the prices oftraded gooas in the international market, real permanent income, real money stock, one period lagged rate of inflation, and changes in the terms of trade between traded and non-traded goods are found to be the major determinants of inflation in Bangladesh.